Islamic finance: an alternative financial system for stability, equity, and growth - Askari, Hossein; Krichene, Noureddine (PSL Quarterly Review, 2014)
Conventional finance has long been plagued by crises that cause economic dislocations and impede sustained economic growth, with banks and non-bank financial institutions requiring periodic bailouts. Numerous developing countries have been unable to mobilise domestic and foreign financial resources for development while many advanced countries continue to be plagued by recurring financial crises. A number of eminent economists have denounced the shortfalls of conventional banking and have advocated 100% reserve banking as the stable foundation for a financial system, a recommendation that happens to coincide with the Islamic financial system. The Islamic financial system is characterised by a two-tier banking system with 100% reserve deposit system and risk-sharing equity or investment banking akin to a mutual fund, and the prohibition of interest and interest-based transactions. Islamic finance promotes risk sharing and an efficient risk-sharing vehicle would be a stock market that operates along Islamic principles that prohibit interest and interest-based leverage. JEL codes: P43, G15, Z12 Keywords: Islamic finance, financial stability, interest, risk sharing